ANALISIS PELAKSANAAN PLP 2 DALAM MENGEMBANGKAN KOMPETENSI PROFESIONAL MAHASISWA PENDIDIKAN BAHASA DAN EKONOMI SEBAGAI CALON GURU - Cheriani; Aisyah; Alfatihani Punna, Putri; Kurnia Fitrah, Arviqa; Ramadhani, Nuriah; Nursyakilah; Rini (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the implementation of the School Field Introduction Program II (PLP II) in developing the professional competence of students in Indonesian Language Education, English Language Education, and Economic Education as prospective teachers. This research employed a qualitative approach with a descriptive method. The subjects consisted of PLP II students from the three study programs. Data were collected through observation, interviews, and documentation, and analyzed using the interactive model of Miles and Huberman. The results indicate that PLP II significantly contributes to the improvement of students’ professional competence, including lesson planning, teaching implementation, and evaluation skills. Language education students demonstrated improvement in communication, literacy, and the use of communicative approaches, while economic education students showed enhanced ability in contextual analysis and simplifying economic concepts. However, several challenges were identified, including limited practice time, variations in mentoring quality, and differing levels of student readiness. In conclusion, PLP II is an effective program in developing the professional competence of prospective teachers through direct field experience, although further optimization is still needed.